Eco-friendly sustainable farming: Enhancing summer tomato (Lycopersicon esculentum mill.) yield with jute non-woven agro textile Mulch - Nilimesh Mridha; Dipak Nayak; Ashok Yadav; Tilak Mondal; Rakesh Kr Ghosh; Manik Bhowmick; Atul Singha; D.P. Ray; B.S. Manjunatha; Avijit Das; D.B. Shakyawar; Sourav Paul; et al. (Heliyon)
Jute-based non-woven was engineered using 50 % pure jute with 50 % caddis (mill waste of jute) on a weight basis. Jute non-woven mulch with 100 % jute (100:0) of 250, 450, and 650 g per square meter (GSM), the blend non-woven of pure jute with caddis (50:50) of 250, 450, and 650 GSM, plastic (50 μm) and rice straw mulch were evaluated on summer tomato crop at the ICAR-CISH regional station in Malda, West Bengal, India. Jute non-woven fabrics of higher thickness with lower water flow and transmissivity increase soil moisture content over no mulch (∼70 %) and plastic mulch (∼9.3 %). The temperature throughout the soil depths for all mulch treatments was lower over no mulch, and for 650 GSM, it was the lowest. Various soil parameters, plant growth parameters, microbial growth, nutrient uptake, and water use efficiency (WUE) under jute non-woven have been improved significantly over no mulch and also over plastic mulch. Jute mulch of 650 GSM, 100:0, followed by 250 GSM, 50:50, and 450 GSM, 100:0, outperformed other mulching materials for tomato yield and fruit quality parameters. The yield of summer tomato crops under jute non-woven (650 GSM, 100:0) has increased significantly by 84 % over no mulch and 28 % over plastic mulch. Therefore, jute non-woven mulch can be a potential alternative to plastic mulch for eco-friendly and sustainable tomato production.